2003
DOI: 10.1590/s0066-782x2003001400003
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of morphology and cardiac function in rats undergoing induction of supravalvular aortic stenosis

Abstract: Ascending aortic stenosis promotes concentric LVH with myocardial fibrosis and minimal histological changes. According to the period of evaluation, cardiac function may be improved, normal, or depressed. The model is suitable and useful for studies on pathophysiology and treatment of the different phases of cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
(29 reference statements)
3
16
0
1
Order By: Relevance
“…The increase of left ventricle wall relative thickness in stenosis group indicates concentric hypertrophy. The data are in agreement with previous studies that showed cardiac remodeling in this experimental model 5,9,11,20 . Remodeling of the left chamber is an adaptive response to ventricular pressure rise; the increase in wall thickness and cavity volume decrease normalize parietal stress and, in consequence, LV function 1,21 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The increase of left ventricle wall relative thickness in stenosis group indicates concentric hypertrophy. The data are in agreement with previous studies that showed cardiac remodeling in this experimental model 5,9,11,20 . Remodeling of the left chamber is an adaptive response to ventricular pressure rise; the increase in wall thickness and cavity volume decrease normalize parietal stress and, in consequence, LV function 1,21 .…”
Section: Discussionsupporting
confidence: 93%
“…The ΔD endo observed at week 6 was similar to that reported by Bregagnollo et al 7,22 , Ribeiro et al 11 and Litwin et al 9 who found an improved systolic function at this time. Furthermore, these authors also observed worsening after 18 or 21 weeks.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At 10 -12 wk postbanding, the animals enter a decompensated stage with depressed LV developed pressure (LVDP) and dP/dt. In this model of LVH, no systemic activation of the sympathetic nervous system or of the renin-angiotensin-aldosterone system occurs (46). Consequently, there are no signs of cardiac lesions, peripheral arteritis, myocardial necrosis, or extensive fibrosis.…”
Section: Methodsmentioning
confidence: 91%
“…This banding procedure relies on the natural growth of the animal to produce a gradually increasing degree of aortic constriction. The rats develop a concentric hypertrophy and increased heart-to-body weight ratio, which is associated, in the short term, with improvement in the systolic function of the heart (27,42,46,48,60). At 10 -12 wk postbanding, the animals enter a decompensated stage with depressed LV developed pressure (LVDP) and dP/dt.…”
Section: Methodsmentioning
confidence: 99%